Free Burma : transnational legal action and corporate accountability - Dale, John G. (University of Minnesota Press, 2011)
When the military's ruling party violently quashed Burma's pro-democracy movement, diplomatic condemnation quickly followed--to little effect. But when Burma's activists began linking the movement to others around the world, the result was dramatically different. This book is the first to explain how Burma's pro-democracy movement became a transnational social movement for human rights. Through the experience of the Free Burma movement, John G. Dale demonstrates how social movements create and appropriate legal mechanisms for generating new transnational political opportunities. He presents three corporate accountability campaigns waged by the Free Burma movement. The cases focus on the legislation of "Free Burma" laws in local governments throughout the United States; the effort to force the state of California to de-charter Unocal Oil Corporation for its flagrant abuse of human rights; and the first-ever use of the U.S. Alien Tort Claims Act to sue a corporation in a U.S. court for human rights abuses committed abroad. Dale's work also raises the issue of how foreign policies of so-called constructive engagement actually pose a threat to the hope of Burma's activists--and others worldwide--for more democratic economic development